Improving Maturity Level of Smart Tourism in Yogyakarta City - Maulidia Dwi Cahyani; Achmad Djunaedi (Journal of Tourism Economics and Policy, 2026)
This study aims to evaluate the maturity level of smart tourism implementation in Yogyakarta City based on three main aspects, namely destination, amenities, and hospitality. This study used a mixed quantitative-qualitative approach. Data were collected through field observations and in-depth interviews with stakeholders from the Yogyakarta City Culture Office, Tourism Office, Development Planning Agency (BAPPEDA), Transportation Office, Fort Vredeburg Museum, and Sonobudoyo Museum. Eleven indicators across six sub-aspects were analyzed and scored on a scale of 1-5 and referring to the Ministry of Communication and Information Technology’s smart city framework, to determine the maturity level into ad-hoc, initial, scattered, integrated, or smart. The results show that the overall maturity level of smart tourism in Yogyakarta City is at the scattered level with an aggregate score of 3.6 out of 5. The destination and amenities aspects each reached the integrated level (score of 4), while the hospitality aspect was at the scattered level (score of 3). The main strengths lie in cultural attractions, increased tourist visits, and the adoption of digital payments. The main challenges are fragmented system integration, particularly in public transportation services and tourism human resources.